Understanding the behavioural determinants of seeking and engaging in care for knee osteoarthritis in persons with type 2 diabetes mellitus: A qualitative study using the theoretical domains framework. Issue 4 (December 2022) - King, Lauren K.; Krystia, Owen; Waugh, Esther J.; MacKay, Crystal; Stanaitis, Ian; Stretton, Jane; Weisman, Alanna; Ivers, Noah M.; Parsons, Janet A.; Lipscombe, Lorraine; Hawker, Gillian A.
Abstract: Objectives: Symptomatic knee osteoarthritis (OA) frequently co-occurs in individuals with type 2 diabetes mellitus (T2DM). In the context of T2DM, OA is often underdiagnosed and undertreated. To elucidate strategies to improve OA care in persons with T2DM, we assessed their perceptions of the barriers and enablers to seeking and engaging in OA care. Design: We conducted semi-structured interviews with 18 individuals with T2DM and symptomatic knee OA in Ontario, Canada. Transcripts were deductively coded using the Theoretical Domains Framework (TDF), an implementation science framework that incorporates theoretical domains of behaviour determinants, which can be linked to behaviour change techniques. Within each of the relevant domains, data were thematically analyzed to generate belief statements. Results: Seven of the TDF domains prominently influenced the behaviour to seek and engage in OA care. Participants described insufficient receipt of OA knowledge to fully engage in care (knowledge), feeling incapable of participating in physical activity due to joint pain (beliefs about capabilities), uncertainty about effectiveness of therapies (optimism) and lack of guidance from health care providers and insufficient access to community programs/supports (environmental context and resources). Key enablers were strong social support (social influences), sources of accountability (behavioural regulation) and experiencing benefit from treatment (reinforcement). Participants did not see concomitant T2DM as limiting the desire to seek OA care. Conclusions: Among individuals with symptomatic knee OA and T2DM, we identified behavioural determinants of seeking and engaging in OA care. These will be mapped to behavioural change techniques to inform development of a complex intervention.